A study of situation awareness-based resource management scheme in cloud environment. (21st January 2020) - Wang, Junshe; Li, Zheng; Zhang, Hongbin; Yi, Yuzi
In view of the defects of the current cloud resource management, which results in low utilisation of resources. This paper proposes a new method for the cloud environment, which is based on situation awareness. Meanwhile it is particularly important to collect historical load data of resources in the process of situation awareness. In order to improve the quality of data acquisition and reduce the burden of the data collection system, a new adaptive data acquisition algorithm is also designed. The proposed scheme comprehensively evaluates the current situation of the use of resources using FAHP (fuzzy analytic hierarchy process). Meanwhile, the cycle of data acquisition is adjusted in real-time, according to the result of resource evaluation. Then, in order to improve the utilisation of resources and achieve its efficient use, the improved BP algorithm is used to forecast the resource requirement of the next time which can provide the basis for rational allocation.